Physiological Functions of Peroxisome Proliferator-Activated Receptor β - Neels, Jaap G.; Grimaldi, Paul A. (Physiological reviews, 2014)
The peroxisome proliferator-activated receptors, PPARα, PPARβ, and PPARγ, are a family of transcription factors activated by a diversity of molecules including fatty acids and fatty acid metabolites. PPARs regulate the transcription of a large variety of genes implicated in metabolism, inflammation, proliferation, and differentiation in different cell types. These transcriptional regulations involve both direct transactivation and interaction with other transcriptional regulatory pathways. The functions of PPARα and PPARγ have been extensively documented mainly because these isoforms are activated by molecules clinically used as hypolipidemic and antidiabetic compounds. The physiological functions of PPARβ remained for a while less investigated, but the finding that specific synthetic agonists exert beneficial actions in obese subjects uplifted the studies aimed to elucidate the roles of this PPAR isoform. Intensive work based on pharmacological and genetic approaches and on the use of both in vitro and in vivo models has considerably improved our knowledge on the physiological roles of PPARβ in various cell types. This review will summarize the accumulated evidence for the implication of PPARβ in the regulation of development, metabolism, and inflammation in several tissues, including skeletal muscle, heart, skin, and intestine. Some of these findings indicate that pharmacological activation of PPARβ could be envisioned as a therapeutic option for the correction of metabolic disorders and a variety of inflammatory conditions. However, other experimental data suggesting that activation of PPARβ could result in serious adverse effects, such as carcinogenesis and psoriasis, raise concerns about the clinical use of potent PPARβ agonists.